Implementasi Program Pelatihan Kader Taruna Melati (PKTM) Ikatan Pelajar Muhammadiyah (IPM) dalam Menanamkan Pendidikan Akhlak (Studi Kasus PC IPM Bangun Purba) - Tito, Dinda Puspita; Azhar, Ihsan Satrya (LP. Ma'arif Janggan Magetan, 2023)
Taruna Melati Cadre Training (PKTM) is a work program of the Ikatan Pelajar Muhammadiyah (IPM) aimed at strengthening moral education among students. This research aims to analyze the implementation of IPM's PKTM program in the Bangun Purba Branch in instilling moral education to IPM cadres through the Taruna Melati Cadre Training (PKTM). The research method used is qualitative research with a case study approach. Data was collected through participatory observation, interviews, and analysis of documents related to the Taruna Melati Cadre Training (PKTM) of the Ikatan Pelajar Muhammadiyah (IPM). In this research, the researcher found a significant contribution in the activities of the Taruna Melati Cadre Training (PKTM) Program of the Ikatan Pelajar Muhammadiyah (IPM) in instilling moral education to the participants. This is because the program is designed to strengthen participants' understanding of moral values and Islamic character. Some of the activities conducted in the Taruna Melati Cadre Training (PKTM) Program of the Ikatan Pelajar Muhammadiyah (IPM) include group prayers, lectures, discussions, learning about the Al-Quran and Hadith, skill development, and various other materials provided.